SENTENCING OF PRISON CRIME AGAINST THEFT WITH A WEIGHT COMMITTED BY A CHILD - Andi Khaedhir K. Petta Lolo; Kamri Ahmad; Nur Fadhillah M (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal